(10-3y)^2
???????????
danielecandidoolivei:
quer o calculo?
Soluções para a tarefa
Respondido por
1
Resposta:
2x + y = 10
-x + 3y =2
-x + 3y = 2
-x = 2 - 3y
x = \frac{2 - 3y}{-1}
−1
2−3y
x = -2 + 3y
2x + y = 10
2 (-2 + 3y) + y = 10
- 4 + 6y + y = 10
6y + y = 10 + 4
7y = 14
y = 14/7 = 2
x = -2 + 3y
x = -2 + 3 . 2
x = -2 + 6
x = 4
Respondido por
1
Resposta:
( 10 - 3y)^2
( -3y + 10 )^2
( - 3y + 10)^2
( - 3y + 10)( -3 y + 10)
- 3y ( -3y + 10) + 10(- 3y + 10)
9y^2 - 30y + 10(- 3y + 10)
9y^2 - 30y -30y + 100
9y^2 - 60y + 100=
9y^2 - 60y + 100
Perguntas interessantes